2019
DOI: 10.1093/ije/dyz017
|View full text |Cite
|
Sign up to set email alerts
|

Pesticide use and risk of non-Hodgkin lymphoid malignancies in agricultural cohorts from France, Norway and the USA: a pooled analysis from the AGRICOH consortium

Abstract: BackgroundPesticides are commonly used in agriculture, and previous studies endorsed the need to further investigate the possible association between their use and risk of lymphoid malignancies in agricultural workers.MethodsWe investigated the relationship of ever use of 14 selected pesticide chemical groups and 33 individual active chemical ingredients with non-Hodgkin lymphoid malignancies (NHL) overall or major subtypes, in a pooled analysis of three large agricultural worker cohorts. Pesticide use was der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
88
0
13

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 115 publications
(122 citation statements)
references
References 48 publications
1
88
0
13
Order By: Relevance
“…( Alavanja et al, 2014 ) Data from two other large cohort studies, which used crop exposure matrices to assess malathion use, also showed no association between use and NHL risk. ( Leon et al, 2019 ) Differences in results between the current study and these cohorts could be due to different times between exposure and disease development (latent period), different uses of products containing malathion over time (including use on animals), different referent populations (general population versus occupationally exposed), or study design (cohort versus case-control).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…( Alavanja et al, 2014 ) Data from two other large cohort studies, which used crop exposure matrices to assess malathion use, also showed no association between use and NHL risk. ( Leon et al, 2019 ) Differences in results between the current study and these cohorts could be due to different times between exposure and disease development (latent period), different uses of products containing malathion over time (including use on animals), different referent populations (general population versus occupationally exposed), or study design (cohort versus case-control).…”
Section: Discussionmentioning
confidence: 82%
“…The observed associations between malathion and risk were robust in the current analysis, however, these too are not consistent with results from other studies. ( Alavanja et al, 2014 ; Leon et al, 2019 ) The AHS reports relative risks (RR) for malathion and FL of RR ever vs. never = 1.3, 95% CI = 0.7, 2.4 (60 cases) and RR high use = 1.6, 95% CI = 0.6, 4.4 (20 cases). ( Alavanja et al, 2014 ) These are similar in magnitude to those reported here in 468 cases, OR ever vs. never = 1.58, 95% CI = 1.11, 2.27, suggesting that if an association truly exists, the magnitude of effect is modest.…”
Section: Discussionmentioning
confidence: 99%
“…The varying prevalence of follicular lymphoma in the case series so far investigated might account for the contradictory ndings across the epidemiological studies. However, the pooled analysis of three agricultural cohorts co-ordinated by the International Agency for research on Cancer (the AGRICOH Consortium), did not nd an excess risk of follicular lymphoma in association with ever exposure to glyphosate [29]. Instead, an excess risk of DLBCL was observed after strati cation by DDT exposure.…”
Section: Discussionmentioning
confidence: 95%
“…Instead, an excess risk of DLBCL was observed after strati cation by DDT exposure. In this study, the exposure assessment differed across cohorts, and it was based mainly on self-reports, which were combined with crop-exposure matrices in the French and Norwegian cohort [29]. A nonsigni cant 40% excess risk of follicular lymphoma was observed among the ever exposed to glyphosate in the French case-control study [21], based on 3 exposed cases and 24 exposed controls.…”
Section: Discussionmentioning
confidence: 99%
“…More recent evidence, including an update of data that were available before the IARC’s evaluation, showed no association between non-Hodgkin lymphoma and glyphosate but instead suggested an increased risk of a rarer leukaemia subtype 45. And a new analysis pooling the three largest cohort studies on pesticides showed an association between glyphosate and one non-Hodgkin subtype 6. These new analyses do not modify the IARC’s evaluation, but they do have implications for quantifying the risk from glyphosate.…”
Section: Changing Circumstancesmentioning
confidence: 99%